Efficient Solar Integrated Doubly Fed Induction Generator for Wind Energy Harnessing - Kumar, Arjun; Shivashankar; Ram, Bhagwan S. (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: Doubly-Fed Induction Generator (DFIG) is a dual input conventional asynchronous device connected across both stator and rotor, which also functions as an electrical transducer consuming up-to 30 % of the generated power during the rotor injection. This is the major concern with respect to the DFIG in terms of effective power generation. Methods: The proposed work provides the solution for this undesirable power loss by connecting the DFIG with an array of solar Photovoltaic (PV) panel through a conventional direct current bus using a boost converter. This research setup can work on the basis of indirect vector control algorithms applied at the rotor and grid converter level in order to maintain the constant DC voltage under arbitrary conditions. Results: Even the variations in voltage and frequency will be controlled with this novel approach. A simulation model of the 300KW solar PV array and a 2MW DFIG system is developed using MATLAB/Simulink environment. Conclusion: Solar and wind energy sources incorporate Maximum Power Point Tracking (MPPT) through their control algorithms resulting in the add on 30-80 KW of solar power for rotor injection compared to the existing system in order to reduce the power rating of the converters and power consumption from the grid.
Keywords: Maximum power point tracking